The cultural language code adaptation by students from East Nusa Tenggara to Javanese culture - Galuh Satrio Prasojo; Suprihatin (LPPM Stikosa-AWS, 2023)
Every human being has a different culture and self-identity. These differences can be adjusted through intercultural communication activities. This study discusses adjusting the language code in intercultural communication for students from Nusa Tenggara Timur (NTT) towards Javanese Culture within the Stikosa-AWS Campus which aims to find out how the process of adjusting the language code in intercultural communication for students from NTT who interact with Javanese people. The method used in this study is a qualitative descriptive method in which to analyze data on cases that occur objects. The research subjects were five students from NTT, one of whom was born in Surabaya and lives near the Stikosa-AWS Campus. The results of this study indicate that verbal and nonverbal are used when adapting the language code between students from NTT to Javanese culture. A dialect is a verbal form that NTT students can adapt due to daily interactions. There are only slight differences in nonverbal forms such as gestures, expressions, accents, intonation, and tempo of NTT students who live in the Javanese ethnic area, namely, only body movements. The processes NTT students can go through with Javanese culture are assimilation and integration. NTT students and the surrounding Javanese community both assimilate without prejudice to each other to gain comfort and peace. The integration process is carried out by maintaining regional language codes but still interacting with each other. The attitude that must be possessed by NTT students and the Javanese community is to emphasize mutual tolerance.